Implementasi Kebijakan Pencegahan Dan Penanggulangan Hiv/Aids Di Kelurahan Talise Kecamatan Mantikulore Kota Palu - Ikram, Dzul Jalali; Kurnia, Intam; Salingkat, Syarif Permana (JPS: Journal of Publicness Studies, 2025)
His study aims to examine the implementation of HIV/AIDS prevention and control policies in Talise Village, Mantikulore District, Palu City. The study uses George C. Edwards III's policy implementation model, which includes aspects of communication, resources, implementer disposition, and bureaucratic structure. This research employs a qualitative method with a descriptive approach. Data was collected through in-depth interviews with relevant stakeholders, such as the Palu City Health Office, Talise Health Center, the Palu City AIDS Prevention and Control Commission (KPA), and several affected community members. Additionally, field observations and document studies were conducted to strengthen the research findings. The results of the study indicate that the HIV/AIDS prevention and control policies in Talise Village have been implemented Fairly well, especially in terms of coordination between government agencies and healthcare service providers. However, there are still some challenges, such as limited resources, a lack of trained medical staff specifically for HIV/AIDS handling, and the persistent stigma towards people living with HIV/AIDS (PLWHA). Communication between agencies is quite effective, but the dissemination of information to the public needs to be improved so that awareness of HIV/AIDS is broader, and stigma can be reduced.